The Reliability-Centered Maintenance (RCM) effect on plant availability and downtime loss in the process industry. Issue 1 (February 2021) - Khasanah, R; Sodikin, I; Penirewod, A P; Rachmad, B; Pratama, N A
Abstract: The process industry needs an optimal preventive maintenance strategy because the even breakdown of one machine can cause an unexpected shutdown for the whole production process. The case study company (CSC), one of the fertilizer companies in Indonesia implements Reliability-centered Maintenance (RCM) as their preventive maintenance strategy to decrease downtime and increase the availability of the production plants. Eversince the RCM implementation started in 2007, there is no study to evaluate the RCM implementation. Relations between the two parameters (downtime loss and availability) are analyzed using the Pearson correlation test as a statistical method to evaluate the RCM implementation. The results of the analysis show that the R-value of downtime loss and availability of K-3 Ammonia and Urea plants are increased, while the R-value of K-4 Ammonia and Urea Plants are decreased. The RCM implemented in K-4 plants should be evaluated respectively, because the decreasing of the correlation means the RCM implementation on the plant still has not met its propose and there are stills hidden factors that affect the availability and downtime loss of the plant, regardless the RCM implementation.